O-GlcNAcylation: A Sweet Hub in the Regulation of Glucose Metabolism in Health and Disease - Gonzalez-Rellan, Maria J.; Fondevila, Marcos F.; Dieguez, Carlos; Nogueiras, Ruben (Frontiers in Endocrinology, 2022)
O-GlcNAcylation is an important posttranslational modification governed by a single pair of enzymes O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). These two enzymes mediate the dynamic cycling of O-GlcNAcylation on a wide variety of cytosolic, nuclear, and mitochondrial proteins in a nutrient- and stress-responsive manner. To maintain proper glucose homeostasis, a precise mechanism to sense blood glucose levels is required, to adapt cell physiology to fluctuations in nutrient intake to maintain glycemia within a narrow range. Disruptions in glucose homeostasis generates metabolic syndrome and type 2 diabetes. In this review we will discuss and summarize emerging findings that points O-GlcNAcylation as a hub in the regulation of systemic glucose homeostasis, and its involvement in the generation of insulin resistance and type 2 diabetes.